Biocompatibility Evaluation of Ionic‐ and Photo‐Crosslinked Methacrylated Gellan Gum Hydrogels: In Vitro and In Vivo Study. Issue 4 (2nd November 2012) - Silva‐Correia, Joana; Zavan, Barbara; Vindigni, Vincenzo; Silva, Tiago H.; Oliveira, Joaquim M.; Abatangelo, Giovanni; Reis, Rui L.
Abstract In this study, the stability and biocompatibility of methacrylated gellan gum hydrogels, obtained either by ionic‐ (iGG‐MA) or photo‐crosslinking (phGG‐MA), were evaluated in vitro and in vivo. Size exclusion chromatography analysis of the methacrylated gellan gum (GG‐MA) powder revealed that molecular weight is lower as compared to the non‐modified material, i.e., low acyl gellan gum. The water uptake and swelling of iGG‐MA and phGG‐MA hydrogels were investigated in phosphate‐buffered saline solution (pH 7.4). The biocompatibility of the hydrogels was firstly evaluated by producing cell‐laden hydrogels. The in vitro cells encapsulation study showed that lung fibroblast cells (L929 cells) and human intervertebral disc (hIVD) cells are viable when cultured within both hydrogels, up to 21 days of culturing. The iGG‐MA and phGG‐MA hydrogels were also subcutaneously implanted in Lewis rats for 10 and 18 days. Tissue response to the hydrogels implantation was determined by histological analysis (haematoxylin‐eosin staining). A thin fibrous capsule was observed around the implanted hydrogels. No necrosis, calcification, and acute inflammatory reaction were observed. The results presented in this study demonstrate that iGG‐MA and phGG‐MA hydrogels are stable in vitro and in vivo, support L929 and hIVD cells' encapsulation and viability, and were found to be well‐tolerated and non‐toxic in vivo.